Financial challenges faced by homestay owners in heritage tourism destination with special reference to Cochin City - P Balasubramanian and Aanchal (International Journal of Advanced Research and Development, 2017)
In this study the main focus is given to the homestay business and the Major challenges faced by them. It helps to determine to what extend heritage tourism contribute to the economic growth and what are the financial challenges faced by the homestay owners in Cochin City. The study covers a period of 10 years from 2006 to 2015 tourist arrival statistics in Cochin City. Both Primary data and secondary data were used for the study. The primary data were collected from the homestay owners, DTPC officials, tourist information centers based on personal interview and using scheduled questionnaire. The secondary data for purpose of the study were collected from books, reports, government publications and internet. There are 174 government approved homestay owners in Cochin City. From which the sample is taken from the three integrated heritage zone i.e. Fort Kochi, Mattanchery, Fort Vypeen which consist of 63 homestay in which I have concentrated for homestay owner in Fort Kochi which is reduced to 61.based on the study the financial challenges faced by homestay owners are high commercial tax, maintenance expenses, staff expenses, no stable income due to seasonal business. The tools used for data analysis are descriptive statistics, ANOVA, Factor analysis.